2012
DOI: 10.1093/nar/gks850
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human Spartan/C1orf124, an ubiquitin-PCNA interacting regulator of DNA damage tolerance

Abstract: Unrepaired DNA damage may arrest ongoing replication forks, potentially resulting in fork collapse, increased mutagenesis and genomic instability. Replication through DNA lesions depends on mono- and polyubiquitylation of proliferating cell nuclear antigen (PCNA), which enable translesion synthesis (TLS) and template switching, respectively. A proper replication fork rescue is ensured by the dynamic ubiquitylation and deubiquitylation of PCNA; however, as yet, little is known about its regulation. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 43 publications
5
127
0
2
Order By: Relevance
“…Based on this observation, we concluded that the DNA-binding box is not essential for the targeting of SPARTAN. This also indicated that the folding of SPARTAN is not affected by this mutation since both the C-terminal UBZ and the PIP boxes are necessary for its correct targeting to PCNA foci [26]. Moreover, to exclude the possibility that the SPARTAN A mutant hetero-oligomerizes in vivo with its endogenous wild-type form, we repeated the experiment on a SPARTAN-depleted cell line as well ( Figure 3B).…”
Section: Dna Binding Is Essential For the Dna Repair Function Of Spartanmentioning
confidence: 95%
See 4 more Smart Citations
“…Based on this observation, we concluded that the DNA-binding box is not essential for the targeting of SPARTAN. This also indicated that the folding of SPARTAN is not affected by this mutation since both the C-terminal UBZ and the PIP boxes are necessary for its correct targeting to PCNA foci [26]. Moreover, to exclude the possibility that the SPARTAN A mutant hetero-oligomerizes in vivo with its endogenous wild-type form, we repeated the experiment on a SPARTAN-depleted cell line as well ( Figure 3B).…”
Section: Dna Binding Is Essential For the Dna Repair Function Of Spartanmentioning
confidence: 95%
“…Proteins were produced as described previously [26]. Proteins were eluted from the beads with 20 mM reduced glutathione in NT buffer, resulting in GST-Flag-Spartan proteins.…”
Section: Plasmids Cloning and Protein Purificationmentioning
confidence: 99%
See 3 more Smart Citations